Advanced level mathematics : financial mathematics - Grinder, Paul; McKay, Velma; Moshenko, Kim; Sarsiat, Ada; British Columbia. Ministry of Advanced Education, Training, and Technology; Centre for Curriculum, Transfer and Technology; BC Open Textbook Project; BCcampus (Province of British Columbia, Ministry of Advanced Education, Skills & Training, 2020)
"We are often faced with questions concerning our finances: Am I saving enough to put my daughter through college? How much will my investment be worth five years from now? Should I pay down my mortgage with weekly or monthly payments? The mathematics of finance allows us to answer these and similar questions. This textbook aligns with Adult Basic Education (ABE) Advanced Level Mathematics"--BCcampus website.
This work is licensed under the Creative Commons Attribution International CC-BY.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on December 18, 2020).
Keywords: Business mathematics -- Textbooks; Mathematics -- Textbooks; Electronic books